2001
DOI: 10.1152/ajpcell.2001.281.2.c649
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of epithelial transport and barrier function by distinct protein kinase C isoforms

Abstract: The phorbol ester phorbol 12-myristate 13-acetate (PMA) inhibits Cl(-) secretion (short-circuit current, I(sc)) and decreases barrier function (transepithelial resistance, TER) in T84 epithelia. To elucidate the role of specific protein kinase C (PKC) isoenzymes in this response, we compared PMA with two non-phorbol activators of PKC (bryostatin-1 and carbachol) and utilized three PKC inhibitors (Gö-6850, Gö-6976, and rottlerin) with different isozyme selectivity profiles. PMA sequentially inhibited cAMP-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 48 publications
11
77
0
Order By: Relevance
“…Significantly, the relocalization of PKCε to the membrane led to a colocalization with claudin-4, a finding consistent with claudin-4 being a target of this kinase. Translocation of activated PKCε to the membrane upon TPA treatment has been shown in other studies [42,55] and alteration of TJs by translocation of PKCε has been shown previously in epithelial cells [42]. Various isoforms of PKC have been implicated in ovarian tumorigenesis and drug resistance [56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Significantly, the relocalization of PKCε to the membrane led to a colocalization with claudin-4, a finding consistent with claudin-4 being a target of this kinase. Translocation of activated PKCε to the membrane upon TPA treatment has been shown in other studies [42,55] and alteration of TJs by translocation of PKCε has been shown previously in epithelial cells [42]. Various isoforms of PKC have been implicated in ovarian tumorigenesis and drug resistance [56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, several studies have demonstrated the involvement of various kinases in the phosphorylation and regulation of claudin proteins [29][30][31][32][33][34][35][36][37], and we have recently shown that phosphorylation of claudin-3 by PKA can affect TJ properties in ovarian cancer cells [38]. Protein kinase C (PKC) isoforms are present in ovarian cancer and are known to modulate TJ function by phosphorylation of the proteins in the complex [24,34,[39][40][41][42][43], but it is unclear whether PKC can directly phosphorylate and regulate claudin proteins. We have previously shown that claudin-4 can be phosphorylated in ovarian cancer cells upon 12-OTetradecanoylophorbol-13-acetate (TPA) stimulation [38], but the exact PKC isoforms involved, the phosphorylation sites on claudin-4, and the consequences of this phosphorylation have remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These data are consistent with our finding that claudin-3 can be phosphorylated in vivo and the observation that this phosphorylation interferes with TJ function. Studies have implicated protein kinase C in the regulation of TJs through phorbol ester stimulation (17,34), but PKA-dependent regulation of TJs has been poorly documented and is more controversial (20). PKA activation has been suggested to have a role in TJ disruption (32), and claudin-3 phosphorylation may represent one of the targets to achieve this physiological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A cell fractionation protocol was used to obtain membrane-soluble proteins, as PKC accumulates in the membrane upon activation (24,25). A549 monolayers seeded on 1.…”
Section: Detection Of Protein Kinase C (Pkc) Activationmentioning
confidence: 99%
“…Lysates were normalized for protein concentration and run on an 8 -16% gradient polyacrylamide gel followed by transference to nitrocellulose. Blots were probed with an anti-phospho-pan PKC Ab (Cell Signaling) followed by incubation with HRP-conjugated goat anti-rabbit Ab and detection with ECL reagent (Pierce/Endogen) (24,25).…”
Section: Detection Of Protein Kinase C (Pkc) Activationmentioning
confidence: 99%